Oxidative Kinetic Resolution of Some Naphtholic Alcohols Mediated by a Chiral Hypervalent Iodine Reagent - Jain, Nikita; Ciufolini, Marco A. (Synthesis, 2018)
A chiral aryl iodide enables the catalytic, oxidative kinetic resolution of various 2-[(3-hydroxy-2-alkyl)propyl]naphthalen-1-ols.
Keywords: alcohols; asymmetric catalysis; hypervalent iodine; kinetic resolution